History of the Development of Philosophy of Science: Epistemology of Education/Educational Thought in the Middle East in Ancient, Middle, Modern and Contemporary Periods - Muslim, Muhammad Irfai Muslim Irfai (IJIS Edu : Indonesian Journal of Integrated Science Education, 2021)
Talking about the philosophy of science, it is necessary to ask yourself a question, the extent to which thisbranch of philosophy has meaning and relevance to urgent and urgent practical problems, which requirepractical solutions, such as the problem of employment opportunities for college graduates, which isincreasingly limited. educational funds and facilities, etc. Along with that, there is an assumption that thepresence of this philosophy of science is too early on the one hand, but it is also considered too late on theother hand. This research uses a literature study method by collecting data from various articles. The resultsillustrate that the development of the Philosophy of Science undergoes changes over time. the changes thatstarted from the prophetic era to the contemporary era in the Middle East experienced struggles in variouscircles and became one bright spot for a better future.